Factors Affecting Irritable Bowel Syndrome in Medical Students - Ellen Fernanda; Andree Kurniawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: Irritable Bowel Syndrome (IBS) is one of the health problems that bring great effects in education, productivity, and socioeconomic life in Indonesia. It accounts for approximately 10.5% of 304 digestive problems in Jakarta, Indonesia. Particular characteristics are known to increase the risk of IBS in individuals, but the study of IBS in Indonesia is still limited in number. The objective of this study is to assess the prevalence and factors affecting Irritable Bowel Syndrome in medical students.Method: This study is a cross sectional study on medical students of Pelita Harapan University, Karawaci, Tangerang on January 2018 until March 2018. Data were obtained with the use of questionnaire of demographic data, ROME IV IBS Criteria, GAD DSM-IV, and PSQI as the instruments with random sampling technique, and statistically tested using Chi-Squared test.Results: A total of 210 samples consist of 54 subjects with IBS (25.7%) with 43 women (79.6%) and 11 men (20.4%). Findings of bivariate analysis are sex (95% CI, 0.751 - 3.346), obesity (95% CI, 0.612 - 2.673), history of drug consumption (95% CI, 1.246 - 6.742), family history of IBS (95% CI, 1.246 - 6.742), anxiety (95% CI, 1.419 - 9.709), and sleep disorder (95% CI, 0.514 - 1.785).Conclusion: The prevalence of IBS in medical students in our institution is 25.7% with history of drug consumption, family history of IBS, and anxiety as factors statistically significant in IBS.